2020
DOI: 10.1155/2020/7930564
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Paediatricians’ Oral Health Knowledge, Behaviour, and Attitude in the United Arab Emirates

Abstract: Aim. Paediatricians’ oral health knowledge is essential for early detection of disease, appropriate advice, and proper referral. Therefore, this study aimed to evaluate the knowledge, behaviour, and attitude of paediatricians practicing in the United Arab Emirates (UAE) regarding children’s oral health. Study Design. Cross-sectional survey. Methods. A questionnaire consisting of 16 questions was completed after piloting by a sample of randomly selected registered UAE paediatricians. Scores of knowledge (out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
3
14
1
Order By: Relevance
“…They were unaware of the transmission of cariogenic bacteria from mother to child and the international recommendations on specific interventions such as fluoride therapy and dental sealants. Other studies have documented similar findings in the knowledge of preventive measures [ 31 35 ], but a better knowledge of transmission was reported in the US and European studies [ 20 , 30 ]. Regarding the first dental visit, AAP and AAPD recommend that all children have their initial dental visit no later than their first birthday [ 2 ].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…They were unaware of the transmission of cariogenic bacteria from mother to child and the international recommendations on specific interventions such as fluoride therapy and dental sealants. Other studies have documented similar findings in the knowledge of preventive measures [ 31 35 ], but a better knowledge of transmission was reported in the US and European studies [ 20 , 30 ]. Regarding the first dental visit, AAP and AAPD recommend that all children have their initial dental visit no later than their first birthday [ 2 ].…”
Section: Discussionsupporting
confidence: 74%
“…They believed that it should be performed during the child's physical examination. This result was high compared to what was previously reported [ 20 , 30 35 ]. According to other researchers, half of their responders recommended children's first dental visits be between the ages of 1 and 3 [ 21 , 22 , 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…However, a systematic scoping review indicated unavailable health knowledge was reported in the literature [ 34 ]. Studies documented lack of requisite health knowledge in clinicians [ 35 ], Nepal diabetes patients [ 36 ], paediatricians [ 37 ], Australian pharmacists [ 38 ], health professionals [ 39 ], primary care physicians [ 40 ], and nurses working in heart failure units [ 41 ]. Even worse, the gaps in oral health knowledge among a sample of pediatricians were reported [ 42 ].…”
Section: Literature Reviewmentioning
confidence: 99%